ANALISIS PELAKSANAAN PEMASARAN WISATA SEJARAH DI GEDUNG JUANG 45 TERHADAP DAYA TARIK WISATA - Regina Rachel; Prayogo Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of historical tourism marketing at Gedung Juang 45 Tambun, Bekasi Regency, and its implications for tourism attractiveness. The study is based on the potential of Gedung Juang 45 as a historical site with educational value, colonial architecture, and narratives of Indonesia’s independence struggle, yet its marketing has not been managed optimally. This research aims to analyze the current implementation of marketing, identify the factors that hinder effective marketing, and explain the role of marketing in strengthening the attractiveness of Gedung Juang 45 as a historical tourism destination. This study uses a descriptive qualitative approach. Data were collected through field observation, interviews with the site manager and surrounding MSME actors, documentation, and literature review. The data were analyzed through data reduction, data display, conclusion drawing, and SWOT analysis supported by IFAS and EFAS matrices. The findings show that the implementation of the 7P marketing mix at Gedung Juang 45 has not been balanced across all elements. The product and place elements are the main strengths because the site offers historical value, authentic architecture, educational collections, and a strategic location near Tambun Station and main road access. However, promotion and people remain the main weaknesses. Digital promotion is not active, official social media channels are rarely updated, and limited human resources reduce the destination’s ability to reach young visitors effectively. This condition also affects tourist perception, as museums are still viewed as less dynamic spaces. The study concludes that increasing tourism attractiveness requires stronger digital promotion, digital storytelling, visual content, collaboration with content creators, and the involvement of local MSMEs. These strategies can strengthen the image of Gedung Juang 45 as an educational, interactive, and sustainable historical tourism destination.